Informed Consent for the Use of AI in the Process of Providing Medical Services - Katarzyna Wałdoch (Review of European and Comparative Law)
It has been for several years now that physicians use medical devices based on artificial intelligence (AI) in their professional practice. The use of these tools makes health services more personalized, tailored to the individual characteristics and needs of the patient. There is also a technological possibility for AI systems to provide patients with information regarding their health condition and treatment methods. The use of medical devices equipped with AI creates new types of risk, including the risk of algorithmic error, the risk of cyber-attack, and the risk of algorithmic mismatch (false-positive or false-negative results). Most patients do not know these tools, so not everyone will trust them. Obtaining informed consent from the patient is a necessary condition for any medical intervention. This study attempts to answer the following questions: (1) Is there a legal possibility to provide AI with the ability to inform the patient about their health condition and proposed treatment methods?; (2) Does the unpredictability and opacity of AI behavior affect the scope of information that should be provided to the patient before medical intervention?; (3) What information should the physician provide to the patient for this consent to be considered informed?; (4) Should the patient always be informed that AI was involved in the diagnosis or therapeutic process? The presented study uses comparative law methodology. American, Belgian and German law are analysed.